Do diálogo dos documentos oficiais dos professores de língua portuguesa ao seu ensino: um estudo de caso da rede municipal de ensino de São Mateus - Lima, Karlamara Mirândola da Paixão (2024)
This dissertation aims to understand how the dialogue between the teacher and the guiding document of Basic Education learning (BNCC) has been woven, in the context of these new times of "multi" forms of communication, contributing to debates and studies about the current scenario of language teaching in its social practices of reading and writing and for teacher training. In this sense, through a qualitative method, using a collaborative case study methodology, based on dialogues (interviews and studies) between a Portuguese Language teacher from the municipal education network of São Mateus and the researcher, a reflection on research concepts is made through the lenses of impressions and perspectives of this participant, but also giving voice to many other teachers. For this, we articulate with the theoretical voices of Street (2014); Neves (1990, 2000); Gualberto (2017); Santos (2020); Antunes (2003); Rojo (2012); Ribeiro, Coscarelli (2023), who advocate new paths for language teaching and learning, including reflecting on it in the BNCC; and discussing relevant points about the continued use of grammar teaching, but as a complement to explore the paths of formation and the use of other languages as important as it is in the processes of informing and communicating; we also hear echoes of Calow (2005), Ribeiro (2021), Soares (2017), talking about multimodality; also with Kalantzis, Cope, Pinheiro (2020) through whom come the voices of Kress; Van Leeuwen (1996), reflecting on the important approaches to reading and writing that understand human communication as multimodal, with texts that emerge within it being multisemiotic, requiring multiliteracies, in Rojo's voice – about the functioning of all compositions and inciting criticality and agency in the reading/production of subjects in all languages - a pedagogy based on design, with a view to linguistic education. The final understandings point to the need for continuous and more qualified teacher training by the education systems, as well as to the condition of the teacher's academic autonomy, so curtailed by these educational power paths.